2017
DOI: 10.1017/s1355617717001266
|View full text |Cite
|
Sign up to set email alerts
|

Response Time Consistency Is an Indicator of Executive Control Rather than Global Cognitive Ability

Abstract: The findings suggest that exceptionally slow responses convey attention lapses through wavering of cognitive control, which strongly correspond to executive functioning tests. General slowing and extremely slow responses predicted processing speed and executive performance beyond age group, indicating that RT metrics are sensitive to differences in cognitive ability. (JINS, 2018, 24, 456-465).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…It has previously been proposed that the right tail of the response time distribution is an integral contributor to RT ISD, and through ex-Gaussian analysis has been associated with neuropsychological measures of executive functioning (Vasquez et al, 2016, 2018). Our findings suggest that reductions in RT ISD for trained responses are due to changes in the leading edge and right tail of the distribution, estimated by μ and τ respectively—effectively tightening the distributional range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has previously been proposed that the right tail of the response time distribution is an integral contributor to RT ISD, and through ex-Gaussian analysis has been associated with neuropsychological measures of executive functioning (Vasquez et al, 2016, 2018). Our findings suggest that reductions in RT ISD for trained responses are due to changes in the leading edge and right tail of the distribution, estimated by μ and τ respectively—effectively tightening the distributional range.…”
Section: Discussionmentioning
confidence: 99%
“…Research has suggested that extremely slow responses within the response distribution are largely responsible for the observed differences in typical measures of RT IIV (Vasquez, Binns, & Anderson, 2018; Vasquez et al, 2016; West et al, 2002; Williams et al, 2005). Given that RT data are usually not normally distributed, typical measures of RT IIV indicating spread (e.g., standard deviation) include slow responses in the right tail.…”
mentioning
confidence: 99%
“…Intraindividual variability can be observed at multiple time scales [1], and yet, the majority of literature has focused on trial-to-trial response variability within a single time point [11,[22][23][24][25]. However, there is some evidence to suggest that intraindividual variability within and across days is positively correlated, signaling potentially similar processes, although the extent of this generalization is unclear [26].…”
Section: Intraindividual Variability In Cognitionmentioning
confidence: 99%
“…Intraindividual variability can be observed at multiple time scales [ 1 ], and yet, the majority of literature has focused on trial-to-trial response variability within a single time point [ 11 , 22 - 25 ]. However, there is some evidence to suggest that intraindividual variability within and across days is positively correlated, signaling potentially similar processes, although the extent of this generalization is unclear [ 26 ].…”
Section: Introductionmentioning
confidence: 99%